Holographic Maps of Earth's Uses of Morphological Phases of Nasiriyah (1869-2023) - Sharida, Lamia Mohsen; Aarash, a. d. Hamid Fifah (Journal of Ecohumanism, 2024)
Many urban processes interact, ultimately affecting the city's morphology, as well as human activity, land uses, and urban form, to varying degrees.Nasiriyah, an Iraqi city, is one of many locations around the world that has seen substantial modifications to the map of urbanization and the shape of the city. The purpose of this study was to analyze the shape of the city of Nasiriyah using three-dimensional maps and build a cartocarbon model by collecting and analysing data on land use sites, shape and structure using modern geographical techniques, in light of the fact that geographical factors influenced the city's growth and development, and the descriptive analysis was carried out to achieve the objectives of investigation and solve the problem. The current distribution of neighborhoods was assessed using Arc Map 10.8.2. The research examined the city's history, development and internal structure, as well as the compatibility of these plans with land uses. The problem was investigated and solved using descriptive analysis and historical approaches. Arc Map 10.8.2 has been used to assess the current distribution of land-use sites, and to detect spatial relationships between them providing digital maps that are 3D in nature and designed to interact with the user. These maps are capable of updating the geographic database of 3D maps with varying levels of research information. Use these three-dimensional models to monitor changes in the morphological stages of the study area. 3D modeling is able to represent information in three dimensions, this ability enables a more realistic and detailed representation of the city.